Cancer immunotherapy strategies that target the cGAS-STING pathway - Tian, Zhuoying; Zeng, Yue; Peng, Yurong; Liu, Junqi; Wu, Fang (Frontiers in Immunology, 2022)
Activation of the cGAS-STING pathway by cytoplasmic DNA induces the production of type I interferons. Recent advances in research suggest that the cGAS-STING pathway is involved in different parts of the cancer-immunity cycle (CIC) to promote or suppress antitumor immune responses. Combination therapy of STING agonists has made certain progress in preclinical as well as clinical trials, but the selection of combination therapy regimens remains a challenge. In this review, we summarize the role of cGAS-STING in all aspects of CIC, and focus on the combination immunotherapy strategies of STING agonists and current unsolved challenges.